(untitled) (Archives of Pediatrics of Uruguay, 2025)
Introduction: there is evidence of the use of medicinal cannabis derivatives (DCM) as a therapeutic alternative for Refractory Epilepsy (RE). Objectives: describe the profile of use, benefits and risks of DCM in the treatment of children and adolescents (NNA) with RD, assisted at the Pereira Rossell Hospital Center between July/2021 and February/2024. Methodology: descriptive, longitudinal, retrospective study through review of histories and interviews with family members at two moments (t1: July/2022 and t2: February/2024). All children under 19 years of age who received DCM were included. The benefits were assessed according to the reduction in frequency and duration of epileptic seizures (EC). Adverse events and accessibility were researched. Results: 15 children and adolescents were included, median age 8 years, 9/15 male, 13/15 carriers of severe chronic encephalopathies. At the beginning of treatment, 12/15 used DCM of industrial origin. The median initial dose was 0.5 mg/kg/day, then 3.5 and 3.7 mg/kg/day at t1 and t2, respectively. All caregivers reported a greater than 50% reduction in the frequency of CE and half of them reported a reduction in the duration of the crises. Even though the hospital pharmacy was the most frequent means of obtaining it, most of them expressed difficulties having access to it. Adverse effects, even though mostly mild, were identified in 8 cases. Conclusions: the majority of children and adolescents presented a good response to treatment with DCM, which was maintained during follow-up. The safety profile was adequate. Treatment accessibility problems were identified.